Development of Student Activity Sheets (SAS) to Practice Each Creativity Characteristics on Redox Reaction with Project Based Learning (PjBL) Model - Fathimah, Aurellia Inin; Mitarlis, Mitarlis (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study aims to determine the feasibility of a Project Based Learning (PjBL) based student activity sheet (SAS) as a learning media on redox reaction material. The feasibility of this SAS is reviewed based on validity, practicality, and effectiveness. The research method used is the research and development model. The product trial design used a one-group pretest posttest. This research was conducted with a total of 29 student in class XI. The research instruments used in this study were SAS validation sheet, student response questionnaire sheet, student activity observation sheet, learning implementation observation sheet, creativity test question sheet, and learning outcome test question sheet. The SAS developed was declared: (1) feasible because it gets a mode score of 4, (2) practical because it gets the results of the student response questionnaire of 97.6%, the results of the observation of student activity and the observation of learning implementation which gets a mode score of 5, (3) effective for training student' creativity because it gets a p-value of 0.000 from the results of the paired sample t-test which shows that the posttest value is higher than the pretest value and there is a significant difference between the pretest and posttest values. The effectiveness of the developed SAS is also supported by the results of the learning outcomes test which get a p-value of 0.000 from the paired sample t-test results which also show that the posttest value is higher than the pretest value and there is a significant difference between the pretest and posttest values. For this reason, PjBL-based SAS on redox reaction material is suitable for use as a learning medium.